IMPACT OF PREOPERATIVE EDUCATIONAL SESSIONS ON ANXIETY AND PAIN OUTCOMES IN CESAREAN SECTION PATIENTS - Dr. Saurabh Mishra; Dr. Indu Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Anxiety and pain are significant concerns for women undergoing cesarean sections. This study aimed to evaluate the effect of the impact of educational interventions on reducing pre-operative anxiety and postoperative pain among cesarean section patients. Methods: A randomized controlled trial was conducted in the OPD Department of Gynaecology & Obstetric, Varun Arjun Medical and Rohilkhand Hospital, involving 90 women scheduled for cesarean sections. Participants were divided into a Group-I (n=45), receiving standard care, and an Group-II (n=45), participating in four educational sessions about the cesarean process and operating room environment. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HAM-A), and pain intensity was measured post-cesarean using Visual Analog Scale (VAS). Results: Group-II subjects reported significantly reduced anxiety post-education (p<0.01), with HAM-A scores decreasing from 17.7 ± 3.2 to 13.6 ± 2.6. Similarly, post-cesarean VAS pain scores were significantly lower in Group-II at 4.8 ± 1.0 compared to Group-I at 6.4 ± 1.4 (p<0.001). Conclusion: The study indicates that educational interventions can effectively reduce anxiety and pain in women undergoing cesarean sections. This suggests incorporating educational programs into pre-operative care may enhance patient experience and recovery outcomes. However, limitations such as the small sample size and the study’s single-centre nature necessitate further research for more generalized conclusions.